Relative effects of porosity and grain size on ultrasonic wave propagation in marbles - Özkan, V.; Sarpün, I. H.; Tuncel, S. (My University, 2012)
Grain size determinations by various ultrasonic techniques have been considered by several researches. Among the known methods, the ultrasonic seems to stand out because the method could be used to determine many properties of the materials. In this paper, we investigated that relative effect of porosity, mean grain size on ultrasonic velocity in marbles. We have represented ultrasonic velocity- porosity and porosity-grain size master graph. Using this graph, we have compared mean grain size of marble samples by optic microscope images. The experimental data are compared with the velocity versus porosity curves calculated according to ultrasonic methods. We see that ultrasonic velocity and porosity has showed a linear relation with the mean grain size of samples. © RILEM 2013.
Keywords: Marble; Mean grain size; Porosity; Ultrasonic velocity; Ultrasounds